(untitled) (The Pakistan Development Review, 2022)
In urban areas across Asia and Africa, public investments in road infrastructure subsidise suburban sprawl and privilege car ownership. At the same time, restrictive land use ordinances prevent mixed-use land development, so distances between home and work increase; an outcome particularly burdensome in time and money for marginal groups. To analyse the effects of public investments in road infrastructure on commute times for different modes, the study uses a rare household travel survey from Lahore. A novel multilevel methodology nests individual-level commute times for different modes within a zone level of analysis which controls for differences in urban land use and road infrastructure. Results suggest that individuals who drive to work enjoy significant time benefits over those who walk to work. The policy implications focus attention on the need for infrastructure investments to mitigate the time costs for commuters who walk and who ride the bus.